DETERMINANTS OF FISCAL RULES IMPLEMENTATION – AN EU CASE STUDY - Onofrei Mihaela; Macsim Florin-Alexandru; Oprea Florin (Annals of the University of Oradea: Economic Science, 2017)
This paper examines the implications of EU treaties, EU accession and other significant variables on the implementation of fiscal rules by EU states at a national level, sample period being years 1994-2015. The four targeted rules are the Budget Balance Rule, Public Debt Rule, Public Expenditure Rule and Public Revenue Rule for general or central governments. Two were our established key hypothesis: first, the fact that EU treaties enhance fiscal discipline at a national level, and second, the fact that the fiscal integration process determined in this particular case by EU accession and the two Maastricht treaty rules has a positive impact too. Both variables exert a positive influence on the implementation of fiscal rules at a national level by EU member states. While levels of public revenues as ratio-to-GDP exert a positive influence on the implementation of the related rules, it also has a negative impact on the implementation of the expenditure rule. Enhancing fiscal discipline through external factors is not necessarily the best method, as it may not correlate with internal structures and aggregates. Nevertheless, our results indicate that treaties and the integration process do bring with themselves fiscal rules that enhance fiscal discipline, fiscal framework, and conduct to more solid public finances.